Management of the psychological comorbidities of dermatological conditions: practitioners' guidelines - Connor CJ (Dove Medical Press, 2017)
Cody J Connor Department of Dermatology, University of Alabama at Birmingham, Birmingham, AL, USA Abstract: Dermatological disease can be devastating for patients, and although dermatologists are focused on remedying the cutaneous manifestations of these conditions, it is easy to miss the psychological suffering lurking below. Studies reveal that psychiatric comorbidity in dermatology is highly prevalent. Undetected psychopathology can greatly decrease a patient’s quality of life and even contribute significantly to the clinical severity of their skin disease. For these reasons, it is vital that practitioners learn to detect psychological distress when it is present, and it is equally essential that they understand the treatment options available for effective intervention. Without training in psychiatric diagnosis and psychopharmacology, dermatologists can easily feel overwhelmed or out of their comfort zone when faced with the need to manage such conditions, but with the negative stigma associated with psychiatric disease in general, a psychiatric referral is often refused by patients, and the dermatologist is thus left with the responsibility. Uncertainty abounds in such situations, but this review seeks to alleviate the discomfort with psychodermatological disease and share practical and impactful recommendations to assist in diagnosis and treatment. In a busy dermatology clinic, the key is effective and efficient screening, combined with a repertoire of pharmacological and non-pharmacological treatment options that can be dispersed through an algorithmic approach according to the specific findings of that screening. By implementing these recommendations into practice, dermatologists may begin to gain comfort with the management of psychocutaneous disease and, as a specialty, may expand to fill a hole in patient care that is truly significant for patients, their families, and our communities as a whole. Keywords: psychodermatology, psychopathology, treatment, screening, comorbidity, quality of life